International R&D Spillovers and Marginal Social Returns on R&D - Kazuo Ogawa; Elmer Sterken; Ichiro Tokutsu (Center for Economic Studies and ifo Institute (CESifo), 2016)
We analyze the impact of international R&D spillovers on recipient countries in terms of social and private returns. We divide the aggregate R&D stock by the business, government and education sectors and examine the impact on Total Factor Productivity. We endogenize the accrual of the R&D stocks by estimating an R&D investment function. We find that the marginal social returns on R&D are much larger than the marginal private returns for R&D-intensive countries. It implies that R&D intensive countries are expected to generate more spillovers at the margin, but the observed R&D stock is smaller than the socially optimal level.
Keywords: E22; O32; O33; O47; 330; R&D; spillovers; total factor productivity; social returns; private returns